2006
DOI: 10.1210/jc.2005-2433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dehydroepiandrosterone and Atamestane Supplementation on Frailty in Elderly Men

Abstract: The results of this double-blind, randomized trial do not support the hypothesis that hormone replacement with DHEA and/or atamestane might improve the course of frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 16 publications
1
64
0
Order By: Relevance
“…It is well established that androgens increase muscle mass in men (26)(27)(28), while the possible role of estrogens and ERs for muscle mass in men remains unclear. Clinical trials investigating the effects of aromatase inhibition in older men showed no effect of the intervention on body composition or muscle strength (29,30) and, thus, did not support an important role of serum E 2 levels for lean mass in men. Nevertheless, animal studies have indicated that not only AR activation but also ER activation modulates lean mass (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 91%
“…It is well established that androgens increase muscle mass in men (26)(27)(28), while the possible role of estrogens and ERs for muscle mass in men remains unclear. Clinical trials investigating the effects of aromatase inhibition in older men showed no effect of the intervention on body composition or muscle strength (29,30) and, thus, did not support an important role of serum E 2 levels for lean mass in men. Nevertheless, animal studies have indicated that not only AR activation but also ER activation modulates lean mass (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 91%
“…Aromatase inhibitors have been used in boys with idiopathic short stature to promote linear growth (24,25), in eugonadal young adults to study metabolic effects (26,27), and in eugonadal and hypogonadal elderly to examine the effect on frailty (26,28,29). The only clinical effect shown thus far is an increase in body height of about 6 cm in boys with idiopathic short stature, i.e.…”
Section: Previous Experience With Aromatase Inhibitionmentioning
confidence: 99%
“…Eight of the 11 studies used specific criteria to select "frail" participants, although these criteria were variously defined. 10e13, 15,16,18,19 In the other three studies, two enrolled people only by age (>70 years) 17,20 and the remaining one enrolled frail or fractured older adults. 14 All studies agreed that decline in physiological reserves is an important component of frailty, although they operationalized the concept differently.…”
Section: Study Population and Frailty Indicatorsmentioning
confidence: 99%
“…11,18,19 Isometric grip strength and leg extensor power were used in one study. 16 Another used the short physical performance battery to evaluate effectiveness of frailty intervention. 10 One study specified the rapid-gait test, stand-up test, and Barthal index as its frailty indicators.…”
Section: Study Population and Frailty Indicatorsmentioning
confidence: 99%